Poland in good constitution? contemporary issues of constitutional law in Poland in the European context - Löhnig, Martin 1971-; Serowaniec, Maciej; Wantoch-Rekowski, Jacek; Moszyńska, Anna 19XX- (Legal area studies, 2023)
In 2022 the Polish Constitution celebrated the silver anniversary of its enactment. It has generally correctly served as the basis for the functioning of the state, proving itself even in the most difficult moments of its existence. Since 2015 the Polish Constitution has been subject to major factual changes to such an extent that it is reasonable to argue that it and Polish constitutionalism in general have come to function in rather unusual, if not downright extreme conditions. This monograph entitled "Poland in good constitution? Contemporary issues of constitutional law in Poland in the European context" aims to present analyses of selected aspects of the impact of the Polish Constitution on individual branches of law and problems occurring in them. All issues are placed in a wide, European context.